IN VITRO ANTIOXIDANT ACTIVITY ON THE ROOT TUBER OF SMILAX CHINA L. - SARAVANA KUMAR S,; CHRISTILDA FELICIA, (International Journal of Pharma and Bio Sciences, 2015)
Many medicinal plants were with a long history of use in folk medicine against a variety of diseases. Recently, many researchers have taken a great interest on medicinal plants for their phytochemical constituents and biological activities including antioxidant activity. The present study was aimed to evaluate phytochemical analysis, quantification of total phenolic, alkaloid contents and antioxidant activity of Smilax china extracts (70% Ethanol, Methanol, Ethyl Acetate and Hexane). The total phenolic and alkaloid contents were quantified by using gallic acid and atropine are as standards and antioxidant activity was evaluated by using three free radicals (Superoxide and DPPH). Smilax china extracts revealed the presence of different phytochemical constituents like steroids, terpenoids, flavanoids, alkaloids, glycosides, tannins, carbohydrates, and amino acids. The methanol extract has more phenolic and alkaloid contents i.e. 38.83±0.68 (mg/gm) and 26.37±0.16 (mg/gm) than other extracts. The extracts were produced concentration dependent percentage inhibition of free radicals and produced maximum activity at concentrations of 800µg. Among all extracts, methanolic extract showed better activity compared to other extracts with mean IC50 values DPPH radicals were 800 µg and 400µg. The above results suggest that Smilax china extracts have antioxidant activity. Further research is in progress i.e. to isolation and characterization of active molecules (compounds) responsible for the antioxidant activity which can be used to treat various diseases.